THE STRENGTHENING MARKETING STRATEGY OF THE PEARL JEWELRY CRAFTS INDUSTRY IN MATARAM DUE TO THE IMPACT OF COVID 19 PANDEMIC - H M Ilhamuddin; Santi Nururly; Rusminah Rusminah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
The purpose of research conducted on the creative industry of pearl jewelry is to analyze the strengthening of industrial marketing strategy due to the impact of covid-19 pandemic in Mataram. The type of research used is qualitative with a descriptive type of approach. Analysis is carried out in three stages, namely: the first stage as a data input stage on the IFE and EFE matrices, the second stage as a matching stage using the SWOT matrix, and the third stage was the formulation of strengthening marketing strategies for the pearl jewelry industry. The results show that this industry actually has a strong foundation to develop in future. Industry capacity and competence have been built for a long time as a legacy from previous generations, pearl quality, and the industry's ability to build networks with partners and consumers outside the region and even abroad can be a source of competitive advantage for the industry going forward. The Covid pandemic as the most dominant threat variable has collapsed the industrial structure, sales have fallen sharply, production activities and supply of raw materials have stopped. Most of the business actors in all production and marketing chains are unemployed. Strengthening the marketing strategy is formulated so that the industry can get out of unusual situations, namely the industry must build core competencies, using social media in marketing, using market places, continuing to build positive perceptions and attitudes about product quality, increasng craftsman creativity in design skills, and providing training to entrepreneurs and merchants on online marketing. Keywords: strategy, marketing, craft, pearl